Low-density lipoprotein receptor–related protein 1 mediates α-synuclein transmission from the striatum to the substantia nigra in animal models of Parkinson’s disease - Hanjiang Luo; Caixia Peng; Chengli Wu; Chengwei Liu; Qinghua Li; Shun Yu; Jia Liu; Min Chen (Neural Regeneration Research)
α-Synuclein accumulation and transmission are vital to the pathogenesis of Parkinson’s disease, although the mechanisms underlying misfolded α-synuclein accumulation and propagation have not been conclusively determined. The expression of low-density lipoprotein receptor–related protein 1, which is abundantly expressed in neurons and considered to be a multifunctional endocytic receptor, is elevated in the neurons of patients with Parkinson’s disease. However, whether there is a direct link between low-density lipoprotein receptor–related protein 1 and α-synuclein aggregation and propagation in Parkinson’s disease remains unclear. Here, we established animal models of Parkinson’s disease by inoculating monkeys and mice with α-synuclein pre-formed fibrils and observed elevated low-density lipoprotein receptor–related protein 1 levels in the striatum and substantia nigra, accompanied by dopaminergic neuron loss and increased α-synuclein levels. However, low-density lipoprotein receptor–related protein 1 knockdown efficiently rescued dopaminergic neurodegeneration and inhibited the increase in α-synuclein levels in the nigrostriatal system. In HEK293A cells overexpressing α-synuclein fragments, low-density lipoprotein receptor–related protein 1 levels were upregulated only when the N-terminus of α-synuclein was present, whereas an α-synuclein fragment lacking the N-terminus did not lead to low-density lipoprotein receptor–related protein 1 upregulation. Furthermore, the N-terminus of α-synuclein was found to be rich in lysine residues, and blocking lysine residues in PC12 cells treated with α-synuclein pre-formed fibrils effectively reduced the elevated low-density lipoprotein receptor–related protein 1 and α-synuclein levels. These findings indicate that low-density lipoprotein receptor–related protein 1 regulates pathological transmission of α-synuclein from the striatum to the substantia nigra in the nigrostriatal system via lysine residues in the α-synuclein N-terminus.